Multi-layer biaxially oriented film and method for manufacturing the same
The multilayer biaxially oriented film, with its specific 4-methyl-1-pentene polymer and copolymer composition in layer A and polypropylene in layer B, addresses the issues of tear resistance and heat seal resistance in conventional films, providing enhanced heat resistance and stretchability.
Patent Information
- Application Number
- JP2023178034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Conventional multilayer biaxially oriented films tend to tear when stretched at high magnification and exhibit significant shrinkage during heat sealing, necessitating improvements in tear resistance and heat seal resistance.
A multilayer biaxially oriented film structure comprising layers A and B, where the A layer is composed of 75-99% by mass of a 4-methyl-1-pentene polymer and 1-25% by mass of a 4-methyl-1-pentene copolymer, optimized for high melting point and intrinsic viscosity, and the B layer includes polypropylene, enhancing heat resistance and stretchability.
The film achieves excellent heat resistance, particularly heat seal resistance with low shrinkage, and maintains integrity without tearing during high-magnification stretching, while also offering good transparency and reduced delamination risk.
Smart Images

Figure 2025068258000001 
Figure 2025068258000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer biaxially oriented film and a method for producing the same. [Background technology]
[0002] It is common to apply a surface protective film to the surface of resin products, metal products, glass products, etc. for building materials or optics to prevent scratches on the surface or the inclusion of foreign matter during transportation, storage, or processing. Surface protective films are required to have various properties depending on the object to be protected, the purpose of protection, the usage environment, etc., in addition to properties such as flexibility and mechanical properties. For this reason, the development of surface protective films is being promoted from various perspectives. For example, a surface protective film mainly made of a polyethylene component (Patent Document 1) and a surface protective film made of a resin composition mainly made of a polypropylene component and containing an oligomer of 4-methyl-1-pentene and 1-decene have been studied (Patent Document 2).
[0003] Biaxially oriented polypropylene films are widely used as packaging and industrial material films because of their light weight, thermal stability, and excellent mechanical properties. However, when used as packaging films, biaxially oriented polypropylene films have a tendency to shrink easily when subjected to heat sealing, and further improvements have been required.
[0004] In order to obtain a film having excellent heat resistance, various attempts have been made to use polymethylpentene polymers, for example, various attempts have been made to combine polypropylene with polymethylpentene polymers. However, it is known that increasing the content of polymethylpentene deteriorates biaxial stretchability, and that delamination (interlayer peeling) occurs when the film is made into a multilayer film. Various attempts have been made to overcome this problem.
[0005] For example, Patent Document 3 discloses a multilayer biaxially stretched film including layer A containing a 4-methyl-1-pentene polymer and polypropylene, and layer B containing polypropylene, and also discloses that this multilayer biaxially stretched film can suppress delamination and has good releasability.
[0006] Furthermore, Patent Document 4 discloses a multilayer biaxially stretched film including a layer containing two types of 4-methyl-1-pentene polymers and a layer containing polypropylene. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2006-116769 A [Patent Document 2] JP 2010-275340 A [Patent Document 3] JP 2018-144351 A [Patent Document 4] JP 2019-001139 A Summary of the Invention [Problem to be solved by the invention]
[0008] It was found that when the conventional multilayer biaxially stretched films are stretched at a high ratio to produce a film, the layer containing the 4-methyl-1-pentene polymer may break or the film may have poor heat resistance, particularly a tendency to shrink when heat-sealed. Thus, there is room for further improvement.
[0009] The present invention has been made in consideration of the above, and has an object to provide a multilayer biaxially stretched film that is less prone to tearing even when stretched at a high ratio, and that has excellent heat resistance, particularly heat sealing resistance (low shrinkage during heat sealing). [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that the above problems can be solved by the following configuration examples, and have completed the present invention. The configuration examples of the present invention are as follows.
[0011] [1] Includes layers A and B, The layer A is 75 to 99 mass% of a 4-methyl-1-pentene polymer (A1) satisfying the following requirements (A1-I) and (A1-II); 1 to 25% by mass of a 4-methyl-1-pentene copolymer (A2) satisfying the following requirements (A2-I) and (A2-II) (wherein the total of the polymer (A1) and the copolymer (A2) is 100% by mass), A multilayer biaxially stretched film comprising a resin composition comprising: Requirement (A1-I): The content of the structural unit (U1) derived from 4-methyl-1-pentene is 90.0 to 100 mol %, and the content of the structural unit (U2) derived from an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0.0 to 10.0 mol % (with the proviso that the total of the structural units (U1) and (U2) is 100 mol %). Requirement (A1-II): Melting point (Tm A1 ) is 200-250℃ Requirement (A2-I): The content of the structural unit (U3) derived from 4-methyl-1-pentene is 65.0 to 96.0 mol %, and the content of the structural unit (U4) derived from an α-olefin having 8 to 20 carbon atoms is 4.0 to 35.0 mol % (with the proviso that the total of the structural units (U3) and (U4) is 100 mol %). Requirement (A2-II): Melting point (Tm A2 ) is not observed or is between 100 and 199°C.
[0012] [2] The multilayer biaxially stretched film according to [1], wherein the structural unit (U2) is a structural unit derived from an α-olefin having 8 to 20 carbon atoms.
[0013] [3] The multilayer biaxially stretched film according to [1] or [2], wherein the B layer comprises two or more layers.
[0014] [4] The multilayer biaxially stretched film according to any one of [1] to [3], wherein the layer B includes a polypropylene layer.
[0015] [5] The multilayer biaxially stretched film according to any one of [1] to [4], wherein the 4-methyl-1-pentene polymer (A1) further satisfies the following requirement (A1-III): Requirement (A1-III): Intrinsic viscosity [η] measured in decalin at 135°C A1 is 0.5-5.0 dl / g
[0016] [6] The multilayer biaxially stretched film according to any one of [1] to [5], wherein the 4-methyl-1-pentene copolymer (A2) further satisfies the following requirement (A2-III): Requirement (A2-III): Intrinsic viscosity [η] measured in decalin at 135°C A2 is 2.0-6.0 dl / g
[0017] [7] The multilayer biaxially stretched film according to any one of [1] to [6], wherein the areal stretching ratio is 30 to 60 times.
[0018] [8] The multilayer biaxially stretched film according to any one of [1] to [7], which is a packaging film.
[0019] [9] A step (1) of obtaining a raw film including layers that will become the A layer and the B layer; and (2) stretching the raw film at an areal stretching ratio of 30 to 100 times; The step (2) includes a step of stretching in the MD direction at 3 to 10 times its original size and a step of stretching in the TD direction at 3 to 10 times its original size. The method for producing the multilayer biaxially stretched film according to any one of [1] to [8]. Effect of the Invention
[0020] According to the present invention, it is possible to provide a multilayer biaxially stretched film which is less prone to tearing even when stretched at a high ratio and which has excellent heat resistance, particularly heat sealing resistance (low shrinkage during heat sealing). Furthermore, according to the present invention, it is possible to provide a multilayer biaxially stretched film that combines good heat resistance and good seal appearance, has good transparency, has good stretchability, and is resistant to delamination (interlayer peeling). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] In this specification, the expression "polymer" is used to encompass homopolymers and copolymers, unless otherwise specified. In addition, in this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower limit or upper limit.
[0022] In this specification, with respect to a certain monomer X, the term "structural unit derived from X" means a structural unit corresponding to the monomer X. For example, the structure of the monomer X is represented by R P R Q C=CR R R S In this case, the "structural unit derived from X" is -CR P R Q -CR R R S For example, "a structural unit derived from 4-methyl-1-pentene" refers to a structural unit corresponding to 4-methyl-1-pentene (i.e., a structural unit represented by -CH2-CH(-CH2CH(CH3)2)-).
[0023] Each component constituting the A layer, B layer, etc. described below (e.g., various compounds that are raw materials for the polymer (A1), the copolymer (A2), and other components) may be a compound derived from a fossil raw material or a compound derived from a biomass. Also, each component constituting the A layer, B layer, etc. described below may be a compound derived from a fossil raw material or a compound derived from a biomass.
[0024] Also, in this specification, when referring to the amount of each component in the composition, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition. In the following description, various physical properties are described, and the details of the measurement conditions for the various physical properties are described in the Examples section.
[0025] ≪Multi-layer biaxially stretched film≫ The multi-layer biaxially stretched film according to the present invention (hereinafter also referred to as "this film") includes a B layer and the following specific A layer. In this specification, the film and the sheet are not particularly distinguished, and the film-like (plate-like) body is generically referred to as a film.
[0026] For example, when using a polypropylene layer, in the film made of the polypropylene layer, it is possible to stretch at a high magnification, but the film made of the polypropylene layer was likely to shrink during heat sealing. Also, since the conventional 4-methyl-1-pentene polymer layer is difficult to stretch at a high magnification, it has been difficult to stretch a multi-layer film including the 4-methyl-1-pentene polymer layer at a high magnification. On the other hand, even when using a polypropylene layer as the B layer, this film includes a specific A layer that is excellent in heat resistance and stretchability. Therefore, even when stretched at a high magnification, tearing or the like is less likely to occur, and a film excellent in heat resistance, particularly heat seal resistance (low shrinkage during heat sealing), can be obtained. Also, since both the polymer (A1) and the copolymer (A2) contained in the A layer contain structural units derived from 4-methyl-1-pentene, the polymer (A1) and the copolymer (A2) are excellent in compatibility, and an A layer excellent in haze can be obtained.
[0027] The layer A contains a resin composition containing 75 to 99 mass % of the following 4-methyl-1-pentene polymer (A1) (hereinafter also referred to as "polymer (A1)") and 1 to 25 mass % of the following 4-methyl-1-pentene copolymer (A2) (hereinafter also referred to as "copolymer (A2)") (the total of the polymer (A1) and copolymer (A2) is 100 mass %). The layer A is not particularly limited as long as it is a layer containing the resin composition, but is preferably a layer made of the resin composition (only).
[0028] As described above, Layer A contains copolymer (A2) in addition to polymer (A1), and thus when made into a multilayer biaxially stretched film, it has flexibility and good stretchability, and also has excellent heat resistance. In addition, the resulting multilayer biaxially stretched film has excellent appearance when subjected to heat sealing.
[0029] Layer A may be composed of a single layer or two or more layers, but is preferably composed of a single layer. When layer A is composed of two or more layers, the two or more layers may be the same layer or different layers.
[0030] [Polymer (A1)] The polymer (A1) satisfies the following requirements (A1-I) and (A1-II). The polymer (A1) may be a homopolymer of 4-methyl-1-pentene or a copolymer of 4-methyl-1-pentene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene), and the latter is preferable. The polymer (A1) used in the resin composition may be one type or two or more types.
[0031] Requirement (A1-I): The content of the structural unit (U1) derived from 4-methyl-1-pentene is 90.0 to 100 mol %, and the content of the structural unit (U2) derived from an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0.0 to 10.0 mol %. Requirement (A1-II): Melting point (TmA1 ) is 200~250℃.
[0032] The content of the structural unit (U1) in the polymer (A1) is 90.0 to 100 mol %, preferably 92.0 to 99.9 mol %, more preferably 94.0 to 99.9 mol %, and even more preferably 95.0 to 99.9 mol %. Furthermore, the content of the structural unit (U2) in the polymer (A1) is from 0.0 to 10.0 mol %, preferably from 0.1 to 8.0 mol %, more preferably from 0.1 to 6.0 mol %, and even more preferably from 0.1 to 5.0 mol %. However, the total of the structural units (U1) and (U2) is 100 mol %, but this 100 mol % does not mean that all structural units constituting the polymer (A1) are 100 mol %.
[0033] The α-olefin having 3 to 20 carbon atoms in the structural unit (U2) is not particularly limited as long as it is an α-olefin having 3 to 20 carbon atoms other than 4-methyl-1-pentene, and specific examples include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, from the viewpoints that the A layer can be stretched to a higher degree and can maintain high transparency even after stretching, α-olefins having 8 to 20 carbon atoms are preferred, linear α-olefins having 8 to 20 carbon atoms are more preferred, and linear α-olefins having 10 to 20 carbon atoms are even more preferred. Specifically, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are preferred, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are more preferred, and 1-decene is even more preferred.
[0034] The polymer (A1) may have only one type of structural unit (U2), or may have two or more types.
[0035] The polymer (A1) may further contain structural units derived from other polymerizable compounds than 4-methyl-1-pentene and the α-olefins having 3 to 20 carbon atoms, provided that the object of the present invention is not impaired. The polymer (A1) may have only one type of structural unit derived from the other polymerizable compound, or may have two or more types of structural units derived from the other polymerizable compound.
[0036] Examples of the other polymerizable compounds include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene. Examples of non-conjugated polyenes include dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.
[0037] In the polymer (A1), the content of the structural units derived from the other polymerizable compounds is usually 10.0 mol % or less, preferably 5.0 mol % or less, and more preferably 3.0 mol % or less, relative to 100 mol % of all structural units constituting the polymer (A1). That is, the total content of the structural units (U1) and (U2) is usually from 90.0 mol% to 100 mol%, preferably from 95.0 mol% to 100 mol%, and more preferably from 97.0 mol% to 100 mol%, based on 100 mol% of all structural units constituting the polymer (A1).
[0038] The melting point (Tm) of polymer (A1) measured by differential scanning calorimetry (DSC)A1 ) is 200 to 250°C, preferably 200 to 245°C, and more preferably 210 to 240°C. The polymer (A1) having a melting point within the above range is preferred from the standpoints of heat resistance, moldability, and the like. The melting point tends to depend on the stereoregularity of the polymer (A1) and the content of the structural unit (U2).
[0039] The polymer (A1) preferably satisfies the following requirement (A1-III). Requirement (A1-III): Intrinsic viscosity [η] measured in decalin at 135°C A1 is 0.5 to 5.0 dl / g. Intrinsic viscosity [η] of polymer (A1) measured in decalin at 135°C A1 is preferably 0.5 to 5.0 dl / g, more preferably 1.0 to 4.0 dl / g, further preferably 1.2 to 3.5 dl / g, and particularly preferably 2.0 to 3.5 dl / g. [η] A1 The polymer (A1) having a viscosity of 100% or more in the above range is considered to exhibit good fluidity during preparation and molding of the resin composition, and further to contribute to improvement of stretchability when combined with the copolymer (A2).
[0040] The content of polymer (A1) in the resin composition is 75 to 99 mass%, preferably 80 to 98 mass%, more preferably 85 to 97 mass%, and even more preferably 88 to 96 mass%, relative to 100 mass% of the total of polymer (A1) and copolymer (A2). When the content of the polymer (A1) is within the above range, a layer A having particularly excellent heat resistance can be easily obtained.
[0041] The polymer (A1) can be produced by a conventional method, for example, the method described in WO 2020 / 116368, WO 2019 / 198694, WO 2017 / 150265, or WO 2006 / 054613.
[0042] [Copolymer (A2)] The copolymer (A2) satisfies the following requirements (A2-I) and (A2-II). The copolymer (A2) used in the resin composition may be one type or two or more types. The copolymer (A2) satisfies the following requirement (A2-I), and in particular has the following structural unit (U4). Therefore, by using such a copolymer (A2), it is possible to easily obtain the present film which has excellent heat resistance, in particular heat sealing resistance, and is unlikely to shrink during heat sealing.
[0043] Requirement (A2-I): The content of the structural unit (U3) derived from 4-methyl-1-pentene is 65.0 to 96.0 mol %, and the content of the structural unit (U4) derived from an α-olefin having 8 to 20 carbon atoms is 4.0 to 35.0 mol %. Requirement (A2-II): Melting point (Tm A2 ) is not observed or is between 100 and 199°C.
[0044] The content of the structural unit (U3) in the copolymer (A2) is 65.0 to 96.0 mol %, preferably 65.0 to 95.0 mol %, more preferably 70.0 to 95.0 mol %, and even more preferably 75.0 to 95.0 mol %. Furthermore, the content of the structural unit (U4) in the copolymer (A2) is 4.0 to 35.0 mol %, preferably 5.0 to 35.0 mol %, more preferably 5.0 to 30.0 mol %, and even more preferably 5.0 to 25.0 mol %. However, the sum of the structural units (U3) and (U4) is 100 mol %, but this 100 mol % does not mean that all structural units constituting the copolymer (A2) are 100 mol %.
[0045] The α-olefin having 8 to 20 carbon atoms in the structural unit (U4) is not particularly limited, but specific examples include 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, linear α-olefins having 8 to 20 carbon atoms are preferred, and linear α-olefins having 10 to 20 carbon atoms are more preferred, in terms of the fact that the A layer can be stretched to a higher degree and can maintain high transparency even after stretching. Specifically, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are preferred, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are more preferred, and 1-decene is even more preferred.
[0046] The copolymer (A2) may have only one type of structural unit (U4), or may have two or more types.
[0047] Copolymer (A2) may further have a structural unit derived from another polymerizable compound other than 4-methyl-1-pentene and an α-olefin having a carbon number of 8 to 20, within the scope of the present invention. Examples of the other polymerizable compound include the same compounds as those exemplified in the section of polymer (A1). The copolymer (A2) may have only one type of structural unit derived from the other polymerizable compound, or may have two or more types.
[0048] In the copolymer (A2), the content of the structural units derived from the other polymerizable compounds is usually 10.0 mol % or less, preferably 5.0 mol % or less, and more preferably 3.0 mol % or less, relative to 100 mol % of all structural units constituting the copolymer (A2). That is, the total content of the structural units (U3) and (U4) is usually from 90.0 mol% to 100 mol%, preferably from 95.0 mol% to 100 mol%, and more preferably from 97.0 mol% to 100 mol%, based on 100 mol% of all structural units constituting the copolymer (A2).
[0049] The melting point (Tm) of copolymer (A2) measured by differential scanning calorimetry (DSC) A2 ) is not observed or is between 100 and 199°C. The absence of an observed melting point means that no crystal melting peak is present in the heat curve in a DSC measurement. When a melting point is observed, the melting point of the copolymer (A2) is preferably from 110 to 198°C, more preferably from 150 to 197°C. By using the copolymer (A2) having a melting point within the above range, a layer A having excellent stretchability can be easily obtained.
[0050] The copolymer (A2) preferably satisfies the following requirement (A2-III). Requirement (A2-III): Intrinsic viscosity [η] measured in decalin at 135°C A2 is 2.0-6.0 dl / g. Intrinsic viscosity [η] of copolymer (A2) measured in decalin at 135°C A2 is preferably 2.0 to 6.0 dl / g, more preferably 2.0 to 5.0 dl / g, and further preferably 2.0 to 3.0 dl / g. [η] A2 The copolymer (A2) having a value of [η] in the above range exhibits good fluidity during preparation and molding of the resin composition, and is considered to contribute to improvement of stretchability when combined with the polymer (A1). A2 When is equal to or more than the above lower limit, the obtained layer A tends to have better stretchability and better rigidity.
[0051] In addition to the above requirements (A2-I) to (A2-III), the copolymer (A2) preferably satisfies the following requirements (A2-IV) and / or (A2-V), and more preferably satisfies the following requirements (A2-IV) and (A2-V). Requirement (A2-IV): The ratio (U4 / U2) of the content (mol %) of the structural unit (U4) to the content (mol %) of the structural unit (U2) is greater than 1.0 and less than 50.0. Requirements (A2-V):[η] A2 / [η] A1is greater than 0.0 and less than or equal to 6.0.
[0052] The ratio (U4 / U2) of the content (mol %) of the structural unit (U4) to the content (mol %) of the structural unit (U2) is preferably greater than 1.0 and less than 50.0, more preferably 1.3 to 10.0, and even more preferably 1.5 to 5.0. The ratio (U4 / U2) being within the above range means that the amount of the structural unit (U4) contained in the copolymer (A2) is greater than the amount of the structural unit (U2) contained in the polymer (A1). By using the polymer (A1) and the copolymer (A2) having the ratio (U4 / U2) within the above relationship, the stretchability of the resulting layer A is improved, which is preferable.
[0053] When two or more types of polymers (A1) are used in the resin composition, the content of the structural unit (U2) in the ratio (U4 / U2) is the product of the mass ratio of the two or more types of polymers (A1) used and the content of the structural unit (U2) in each polymer (A1). For example, when 30 mass% of polymer (A1-a) having a content of structural unit (U2) of 5 mol% and 70 mass% of polymer (A1-b) having a content of structural unit (U2) of 10 mol% are used as polymer (A1) for use in the resin composition, the content of structural unit (U2) in the ratio (U4 / U2) is 5×0.30+10×0.70=8.5 mol%. In the case where two or more types of copolymers (A2) are used in the resin composition, the content of the structural unit (U4) in the ratio (U4 / U2) is the same.
[0054] The above [η] A1 For the above [η] A2 Ratio of ([η] A2 / [η] A1 ) is preferably greater than 0.0 and equal to or less than 6.0, more preferably 0.3 to 3.0, and even more preferably 0.5 to 1.0.
[0055] In addition, when two or more kinds of polymers (A1) are used in the resin composition, the ratio ([η] A2 / [η] A1 ) in [η]A1 is the mass ratio of two or more polymers (A1) used and the [η] of each polymer (A1) A1 Let it be multiplied by . For example, the polymer (A1) used in the resin composition may have a molecular weight of [η] A1 30% by mass of polymer (A1-c) having a molecular weight of 1.0 dl / g and [η] A1 When 70% by mass of polymer (A1-d) having a molecular weight of 4.0 dl / g is used, the ratio ([η] A2 / [η] A1 ) in [η] A1 is 1.0 x 0.30 + 4.0 x 0.70 = 3.1 dl / g. When two or more types of copolymers (A2) are used in the resin composition, the ratio ([η] A2 / [η] A1 ) in [η] A2 The same is true.
[0056] The content of copolymer (A2) in the resin composition is 1 to 25 mass%, preferably 2 to 20 mass%, more preferably 3 to 15 mass%, and even more preferably 4 to 12 mass%, relative to 100 mass% of the total of polymer (A1) and copolymer (A2). When the content of copolymer (A2) is within the above range, layer A having particularly excellent stretchability can be easily obtained, and the present film having excellent interlayer strength and being resistant to delamination can be easily obtained.
[0057] The copolymer (A2) can be produced by a conventional method, for example, the method described in WO 2020 / 116368, WO 2019 / 198694, WO 2017 / 150265, or WO 2006 / 054613.
[0058] [Other ingredients] The resin composition may be a composition consisting of only the polymer (A1) and the copolymer (A2), and may further contain other components other than the polymer (A1) and the copolymer (A2), as necessary, within the scope of the object of the present invention. Examples of the other components include resins and additives other than the polymer (A1) and the copolymer (A2). The total content of the polymer (A1) and the copolymer (A2) in the resin composition is preferably 60% by mass or more, more preferably 70% by mass or more, relative to 100% by mass of the resin composition, in order to better exhibit the effects of the present invention, and the upper limit is 100% by mass.
[0059] Other resins Examples of the other resins include polyolefin polymers such as polyethylene, poly-1-butene, styrene resins, and ethylene-α-olefin copolymers. The other resins may be used alone or in combination of two or more. When other resins are blended into the resin composition, the amount of the other resins blended is preferably 40% by mass or less, more preferably 30% by mass or less, relative to 100% by mass of the resin composition, with the lower limit being 0% by mass.
[0060] Additives Examples of the additives include weather stabilizers, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, antioxidants, hydrochloric acid absorbers, inorganic or organic fillers, foaming agents, crosslinking agents, crosslinking assistants, adhesives, softeners, flame retardants, secondary antioxidants, natural oils, synthetic oils, and waxes. The additives may be used alone or in combination of two or more kinds.
[0061] [Method for preparing resin composition] The resin composition can be prepared, for example, by mixing the polymer (A1) and the copolymer (A2) with, if necessary, the other components. The mixture of polymer (A1) and copolymer (A2) can also be obtained by a multi-stage polymerization method.
[0062] Regarding the method of mixing the components, various well-known methods can be used, for example, methods of mixing the components using apparatuses such as a plastomill, a Henschel mixer, a V-blender, a ribbon blender, a tumbler, a blender, a kneader extruder, etc. Also, after the mixing, the obtained mixture is further melt-kneaded (e.g., at 180 to 300 °C) using apparatuses such as a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc., and then the obtained melt-kneaded product is granulated or pulverized, whereby high-quality resin composition pellets in which the components are uniformly dispersed and mixed can be obtained.
[0063] The B layer is not particularly limited, and examples thereof include a layer provided to impart excellent mechanical properties (e.g., excellent sealing properties) to the film. The B layer may be composed of a single layer or two or more layers, but from the viewpoints of thickness control, improvement of seal strength, imparting of other functions, etc., it is preferably composed of two or more layers. When the B layer is composed of two or more layers, the two or more layers may be the same layer or different layers. The B layer preferably contains polypropylene (B).
[0064] [Polypropylene (B)] The polypropylene (B) is a known polymer mainly composed of propylene, and specific examples thereof include a propylene homopolymer, a propylene·α-olefin copolymer of propylene and an α-olefin other than propylene (e.g., a propylene random copolymer such as a propylene·ethylene copolymer, a propylene·1-butene copolymer, a propylene·ethylene·1-butene copolymer, a propylene block copolymer, or a mixture thereof).
[0065] In this specification, when a monomer serving as a raw material for a polymer is designated as X, a "polymer mainly composed of X" refers to a polymer which contains the largest number of structural units derived from X among all structural units contained in the polymer. For example, a "polymer mainly composed of propylene" refers to a polymer which contains the largest number of structural units derived from propylene (i.e., structural units represented by -CH2-CH(-CH3)-) among all structural units of the polymer.
[0066] As the polypropylene (B), isotactic polypropylene and syndiotactic polypropylene are preferably used, and the isotactic mesopentactic fraction (mmmm) or syndiotactic mesopentactic fraction (rrrr), which indicates stereoregularity, is preferably 90% or more, more preferably 92% or more, and even more preferably 93% or more. Propylene having high stereoregularity has high resin crystallinity, and by using this propylene, the present film having high thermal stability and mechanical properties can be easily obtained.
[0067] The copolymerization ratio of the α-olefin in the propylene-α-olefin copolymer is preferably 5 mass % or less. The propylene-α-olefin copolymer may be a random copolymer or a block copolymer, and may contain a nucleating agent (crystallization nucleating agent). The nucleating agent is not particularly limited, and examples thereof include α-crystal nucleating agents such as various inorganic compounds, various carboxylic acids or metal salts thereof, dibenzylidene sorbitol compounds, aryl phosphate compounds, mixtures of cyclic polyvalent metal aryl phosphate compounds with alkali metal salts of aliphatic monocarboxylic acids or basic compounds (e.g., basic aluminum compounds, basic lithium compounds, basic hydroxy compounds, basic carbonate compounds, basic hydrate compounds), various polymer compounds, etc. These nucleating agents may be used alone or in combination of two or more.
[0068] The MFR of the polypropylene (B) measured in accordance with JIS K 7210 (temperature: 230° C., load: 2.16 kg) is preferably 0.5 to 25 g / 10 min, more preferably 1 to 15 g / 10 min, and further preferably 2 to 10 g / 10 min. When the MFR of the polypropylene (B) is within the above range, it is suitable for extrusion molding.
[0069] The ash content of polypropylene (B) due to polymerization catalyst residues and the like is preferably as low as possible in order to reduce minute foreign matter (fish eyes) in the present film. Specifically, the ash content is preferably 50 ppm or less, and more preferably 40 ppm or less. When the ash content is within the above range, minute foreign matter and defects in the present film are significantly reduced, and contamination can be reduced when the present film is used for electronic components and the like.
[0070] When the B layer is composed of two or more layers and includes a first B layer (hereinafter also referred to as "B1 layer") and a second layer (hereinafter also referred to as "B2 layer"), the present film may include two or more B layers in the order of, for example, B1 layer, A layer, B2 layer (B1 layer / A layer / B2 layer), or may include two or more B layers in the order of A layer, B1 layer, B2 layer (A layer / B1 layer / B2 layer). Here, when the B1 layer and the B2 layer contain polypropylene (B), the polypropylene (B) constituting the B1 layer (hereinafter also referred to as "polypropylene (B1)") and the polypropylene (B) constituting the B2 layer (hereinafter also referred to as "polypropylene (B2)") may be the same or different.
[0071] When the present film includes two or more B layers in the order of A layer, B1 layer, B2 layer (A layer / B1 layer / B2 layer), and when the polypropylene (B1) and the polypropylene (B2) are different, the melting point of the polypropylene (B1) is preferably equal to or higher than the melting point of the polypropylene (B2), and more preferably, the melting point of the polypropylene (B1) is higher than the melting point of the polypropylene (B2). In this case, for example, the polypropylene (B1) is a propylene homopolymer, and the polypropylene (B2) is a propylene random copolymer.
[0072] When the B layer contains polypropylene (B), the B layer may be a layer made of only polypropylene (B) or a layer made of a resin composition containing polypropylene (B). Here, the resin composition forming the B layer may contain the same components as those listed as other components in the column for the A layer. When layer B is composed of two or more layers, the other components that can be contained in the two or more layers and the amounts of the other components included therein may be the same or different.
[0073] <Composition of this film> The present film may have a layer structure consisting of only layer A / layer B, or may further include layer C which is different from both layer A and layer B. The C layer may be composed of a single layer or may be composed of two or more layers. When the C layer is composed of two or more layers, the two or more layers may be the same layer or different layers.
[0074] A preferred embodiment of the present film is a two-layer structure consisting of layer A / layer B, in which the layer B is a single layer (hereinafter also referred to as "layer B0"). The layer B functions, for example, as a seal layer. In another preferred embodiment of the present film, Layer B is composed of two or more layers, for example, a three-layer structure in which Layer A / Layer B1 / Layer B2 are laminated in this order. The Layer B2 functions, for example, as a seal layer.
[0075] A suitable example of the two or more layers constituting layer B is a layer containing the same resin. The two or more layers constituting layer B function as a sealing layer. Another preferred example of the two or more layers constituting layer B is that at least two layers are different layers. For example, layer B1 and layer B2 may differ depending on the presence or absence and type of components other than the polypropylene (B), or may differ depending on the type of polypropylene (B).
[0076] Examples of the layer C include layers other than the layers A and B that can function appropriately as a sealing layer, such as layers made of ethylene-based resins such as low-density polyethylene (LDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, and ethylene-(meth)acrylic acid copolymer, and blend resins of polyethylene and polybutene. An example of the present film containing the layer C is a three-layer structure in which layer A / layer B / layer C are laminated in this order.
[0077] The total thickness of the present film is preferably 0.1 to 120 μm, more preferably 1 to 40 μm, and even more preferably 1 to 20 μm, from the viewpoints of excellent transparency and mechanical properties.
[0078] The total thickness of layer A in the present film is preferably 0.1 to 20 μm, more preferably 0.3 to 20 μm, and even more preferably 0.5 to 10 μm, from the viewpoint that the present film having an excellent balance between stretchability and heat seal resistance can be easily obtained. When the present film contains two or more A layers, the thickness of each A layer may be the same or different.
[0079] The total thickness of layer B in the present film is preferably 0.1 to 100 μm, more preferably 1 to 20 μm, and even more preferably 1 to 10 μm, from the viewpoint that the present film having a well-balanced excellent stretchability and heat seal resistance can be easily obtained. When the film contains more than one B layer, the thickness of each B layer may be the same or different. In order to easily obtain a present film having an excellent balance between stretchability and heat seal resistance, the thickness of the B1 layer in the present film is preferably 1 to 50 μm, more preferably 1 to 15 μm, and the thickness of the B2 layer in the present film is preferably 0.1 to 50 μm, more preferably 0.1 to 15 μm.
[0080] The thickness of one layer A in the present film is preferably 0.1 to 250%, more preferably 0.5 to 100%, relative to the total thickness of the entire B layer (100%).
[0081] When the present film is heat sealed (temperature: 180°C, gauge pressure: 0.2 MPa, heat sealing time: 1 second), the shrinkage rate of the film in the TD direction is preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less.
[0082] <Application> Specific applications of the present film include, for example, the following general film applications: Packaging films (e.g. food packaging films, stretch films, wrap films, shrink films, easy-peel films, aluminum-deposited films, PVDC-coated films); Breathable films (e.g. films used for disposable diapers, sanitary products, surgical gowns, surgical gloves, surgical down, house wrap (breathable waterproof sheet), disposable hand warmers, household dehumidifiers, desiccants, oxygen absorbers, freshness preserving agents, composting sheets, simple jumpers, etc.); Anti-rust film (e.g., films used as transport packaging, storage packaging, export packaging, etc. for automobile parts, knockdown parts, machinery and machine parts, iron and chrome products, steel pipes, wire rods, bolts and nuts, bearings, molds, tools, blades, cutting tools, construction tools, etc.); Anti-fog films (e.g. films for fruits and vegetables, films for processed foods); Oriented film; films used as confectionery twist packaging, agricultural materials, laminate substrates, coin packaging, electric wire bundling materials, fruit and vegetable packaging, cardboard cutting tape, detergent refill containers, rice ball packaging, pillow packaging, stick packaging, boiled and retort packaging, water food packaging, infusion bags, etc.); Self-cleaning films (e.g. films used for road signs, general signs, billboards, windows, road materials, side mirrors, etc.); Separators (e.g. battery separators, separators for lithium-ion batteries, electrolyte membranes for fuel cells, adhesive and bonding separators); Oriented films (e.g. films for film capacitors, capacitor films, capacitor films for fuel cells); Semiconductor processing films (e.g. dicing tape, back grinding tape, die bonding film, polarizing plate film, surface protection film (e.g. polarizing plate protection film, LCD panel protection film, optical component protection film, lens protection film, electrical component and appliance protection film, mobile phone protection film, PC protection film, masking film, touch panel protection film)); Films for electronic components (e.g. diffusion films, reflective films, radiation-resistant films, gamma-ray-resistant films, porous films); Building material films (e.g. window films for building materials, films for laminated glass, bulletproof materials, films for bulletproof glass, heat-shielding sheets, heat-shielding films); Transfer film (e.g. automotive and industrial transfer film, packaging transfer film); Release films (e.g., release films for flexible printed circuit boards (FPC), release films for ACM boards, release films for rigid-flex boards, release films for advanced composite materials, release films for curing carbon fiber composites, release films for curing glass fiber composites, release films for curing aramid fiber composites, release films for curing nanocomposite materials, release films for curing filler materials, release films for semiconductor encapsulation, release films for polarizing plates, release films for diffusion sheets, release films for prism sheets, release films for reflective sheets, cushion films for release films, release films for fuel cells, release films for various rubber sheets, release films for urethane curing, release films for epoxy curing (e.g., manufacturing process components such as metal bats and golf clubs)).
[0083] Among these, the present film is particularly suitable for use as a packaging film. When the present film is used as a packaging film, a packaging film having excellent appearance even after heat sealing can be easily obtained.
[0084] <Manufacturing method of multilayer biaxially stretched film> The method for producing the present film is not particularly limited, but typically includes a method in which a raw film (film before biaxial stretching) is formed by laminating layers that will become the A layer and the B layer, and optionally a layer that will become the C layer, and then the raw film is biaxially stretched. A method including the following steps (1) and (2) is preferred. Step (1): A step of obtaining a raw film including layers that will become the A layer and the B layer. Step (2): A step of stretching the raw film at an areal magnification of 30 to 100 times, the step including a step of stretching in the MD direction at 3 to 10 times and a step of stretching in the TD direction at 3 to 10 times.
[0085] The method for obtaining the raw film in the step (1) may be, for example, a method in which another film is laminated onto a film previously obtained by T-die molding or inflation molding, etc., by a known lamination method such as extrusion lamination or extrusion coating, or a method in which a plurality of films are independently molded and then each film is laminated by dry lamination. From the viewpoint of productivity, etc., preferred is co-extrusion molding in which the components forming each layer are fed into a multilayer extruder and molded. When forming a raw sheet by the co-extrusion molding, for example, the components forming each layer (for example, pellets of a resin composition) are melt-extruded at a cylinder temperature usually in the range of 180 to 300°C.
[0086] The thickness of the raw film is not particularly limited, but is usually 100 to 1000 μm, preferably 150 to 800 μm, and more preferably 200 to 500 μm.
[0087] The thickness of one layer that will become the A layer in the raw film is preferably 0.1 to 250%, more preferably 0.5 to 100%, relative to the total thickness (100%) of the layers that will become the B layer. The layer that will become layer A is a layer that constitutes the original film and is the layer that will become layer A after biaxial stretching, and the layer that will become layer B is a layer that constitutes the original film and is the layer that will become layer B after biaxial stretching.
[0088] The method for biaxially stretching the raw sheet in the step (2) may be batch-type biaxial stretching, sequential biaxial stretching, or simultaneous biaxial stretching. For example, a specific example of a method of sequential biaxial stretching is to pass an original sheet between rolls maintained at 100 to 165°C and having a speed difference to stretch it 3 to 10 times in the MD direction (flow direction) when the original sheet was formed, and then introduce the film stretched in the MD direction into a tenter and stretch it 3 to 10 times in the TD direction (width direction) when the original sheet was formed at a temperature of 150°C or higher, followed by relaxing, heat setting, and winding.
[0089] The stretching ratio in the MD direction varies depending on the apparatus used, but is preferably 3 to 10 times, and more preferably 5 to 10 times. The stretching ratio in the TD direction varies depending on the apparatus used, but is preferably 3 to 10 times, and more preferably 5 to 10 times. In the step (2), the MD direction and the TD direction are the MD direction (machine direction) and the TD direction (width direction) when the raw sheet is formed. Depending on the method of forming the raw film, there may be no MD direction and TD direction, but in this case, since the MD direction is equal to the TD direction, for the sake of convenience, one of the length and width directions of the raw film is the MD direction, and the other direction is the TD direction.
[0090] The areal magnification in the step (2) is preferably 30 to 80 times, more preferably 30 to 60 times, and further preferably 35 to 50 times. According to the present film, even when stretched at such a high ratio, a desired multi-layer biaxially stretched film that is less prone to tearing or the like can be easily obtained. EXAMPLES
[0091] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these in any way.
[0092] Determination method Various physical properties were measured as follows.
[0093] [Content of constituent units] The contents of the structural units (U1) and (U3) derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A1) and the 4-methyl-1-pentene copolymer (A2), and the contents of the structural units (U2) derived from an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) and the structural units (U4) derived from an α-olefin having 8 to 20 carbon atoms, were determined by the following apparatus and conditions: 13 Calculated from C-NMR spectrum.
[0094] The AVANCEIIIcryo-500 nuclear magnetic resonance spectrometer manufactured by Bruker Biospin was used. The solvent was a mixed solvent of o-dichlorobenzene / benzene-d6 (4 / 1 v / v), the sample concentration was 55 mg / 0.6 mL, the measurement temperature was 120 °C, and the observed nuclei were 13 C (125 MHz), sequence was single pulse proton broadband decoupling, pulse width was 5.0 μsec (45° pulse), repetition time was 5.5 sec, and the number of accumulations was 64. The chemical shift was measured with 128 ppm of benzene-d6 as the reference value. Using the integral value of the main chain methine signal, the content of the structural unit derived from 4-methyl-1-pentene (hereinafter also referred to as "4-methyl-1-pentene content". Corresponding to the structural units (U1) and (U3).) and the content of the structural unit derived from α-olefin (hereinafter also referred to as "α-olefin content". Corresponding to the structural units (U2) and (U4).) were calculated by the following formula. The results are shown in Table 1.
[0095] 4-Methyl-1-pentene content (mol%)=[M / (P+M)]×100 α-Olefin content (mol%)=[P / (P+M)]×100 Here, P represents the total peak area of the main-chain methine signals of α-olefins other than 4-methyl-1-pentene, and M represents the total peak area of the main-chain methine signals of 4-methyl-1-pentene.
[0096] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. Specifically, about 20 mg of the polymer produced in the following Production Example was dissolved in 15 mL of decalin, and the specific viscosity η sp The specific viscosity η sp After measuring the decalin solution, add 5 mL of decalin solvent to dilute it, and measure the specific viscosity η sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0)
[0097] [Melting point (Tm), heat of fusion (ΔHm)] An endothermic curve was obtained using a DSC measuring device (DSC220C) manufactured by Seiko Instruments Inc., and the melting point (Tm) and heat of fusion (ΔHm) were measured as follows. Approximately 5 mg of the (co)polymer was packed in an aluminum pan for measurement, and the temperature was raised to 280°C at 10°C / min. After holding at 280°C for 5 minutes, the temperature was lowered to 20°C at 10°C / min. After holding at 20°C for 5 minutes, the temperature was raised again to 280°C at 10°C / min to obtain a melting (endothermic) curve. The temperature at the apex of the crystal melting peak observed during the second heating was taken as the melting point (Tm). The heat of fusion (ΔHm) was calculated from the integrated value of this crystal melting peak. When multiple peaks were detected during the measurement, the temperature at the peak detected on the highest temperature side and the integrated value of the peaks were taken as the melting point (Tm) and the heat of fusion (ΔHm), respectively.
[0098] [Production Examples 1 to 4: Production of Polymers (A1-1) to (A1-2) and Copolymers (A2-1) to (A2-2)] In accordance with the method described in Comparative Example 1 of WO 2017 / 150265, the α-olefin type was changed to the α-olefins listed in Table 1 below, and the proportions of 4-methyl-1-pentene, α-olefin, and hydrogen used were changed so that the physical properties of the resulting polymers would be the values listed in Table 1 below. Polymers (A1-1) to (A1-2) and copolymers (A2-1) to (A2-2) were produced.
[0099] [Table 1] In Table 1, "-" indicates that the corresponding physical property value was not observed. Moreover, the value of "α-olefin content (mass %)" in Table 1 is calculated from the value of "α-olefin content (mol %)" in the same table.
[0100] [Example 1] [Preparation of resin composition] A mixture was obtained by blending 90 parts by mass of the polymer (A1-1) obtained in the above-mentioned manufacturing example and 10 parts by mass of the copolymer (A2-1) with 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as a secondary antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer. The resulting mixture was then granulated using a twin-screw extruder BT-30 (screw diameter 30 mmφ, L / D = 46) manufactured by Plastics Engineering Research Institute Co., Ltd. under conditions of a set temperature of 270°C, a resin extrusion rate of 60 g / min and 200 rpm to prepare pellets of the resin composition.
[0101] [Preparation of original film] Multilayer films were produced using a three-type, three-layer T-die sheet molding machine (manufactured by Thermo Plastics Industries Co., Ltd.) equipped with a T-die with a lip width of 330 mm, three hopper inlets, and a 30 mm diameter screw. The pellets of the resin composition prepared above were charged into a hopper for layer A, and the cylinder temperature was set to 270°C. In addition, polypropylene (Prime Polypro F113G, manufactured by Prime Polymer Co., Ltd., melting point: 163°C, MFR (230°C, 2.16 kg load): 3.0 g / 10 min) was placed in the hopper for the B1 layer, and polypropylene (Prime Polypro F327, manufactured by Prime Polymer Co., Ltd., melting point: 138°C, MFR (230°C, 2.16 kg load): 7.0 g / 10 min) was placed in the hopper for the B2 layer, and the cylinder temperatures of the hoppers for the B1 layer and B2 layer were each set to 230°C. The die temperature was set to 270°C, and the molten mixture of the resin composition and polypropylene was extruded from the T-die as a multilayer film. The film was then pulled up at a take-up speed of 2.5 m / min while being adhered to a metal cooling roll controlled at 80°C by air pressure, thereby obtaining a cooled and solidified unstretched multilayer film (raw film) having a layer structure of A layer / B1 layer / B2 layer with a thickness of 400 μm. The obtained raw film was a laminate in which an A layer containing the resin composition having a thickness of 80 μm, a B1 layer having a thickness of 240 μm, and a B2 layer having a thickness of 80 μm were laminated in this order. The thickness of each layer was calculated from the extrusion amount.
[0102] [Preparation of multi-layer biaxially stretched film] The raw film thus produced was biaxially stretched using a batch-type biaxial stretching machine (Bruckner, KARO IV). Specifically, the raw film was stretched 5 times in the machine direction (MD) to obtain a uniaxially stretched film under the stretching conditions of preheating temperature 160°C, preheating time 60 seconds, stretching temperature 160°C, stretching speed 238% / sec, and heat setting conditions of 170°C, 30 seconds. Next, under the same conditions, the obtained uniaxially stretched film was stretched 8 times in the transverse direction (TD) to produce a multilayer biaxially stretched film.
[0103] [Example 2 and Comparative Examples 1 to 4] Raw films and biaxially stretched films were prepared in the same manner as in Example 1, except that the types and amounts of the polymers and / or copolymers used were changed as shown in Table 2, and evaluations were carried out. The hPP used in Comparative Example 1 was polypropylene (Prime Polypro F113G, manufactured by Prime Polymer Co., Ltd., melting point: 163° C., MFR (230° C., 2.16 kg load): 3.0 g / 10 min).
[0104] <Stretchability> When the raw film was stretched as described above, the stretchability was evaluated as good (◯) when the entire multilayer biaxially stretched film obtained could be stretched without breaking, and as poor (×) when the film broke and a stretched film could not be obtained. The results are shown in Table 2. When the raw film produced in Comparative Example 2 was used, a stretched film was not obtained, and therefore the following tests for haze and the like could not be performed.
[0105] <Haze> A test piece having a length of 80 mm and a width of 50 mm was taken from the produced multilayer biaxially stretched film, and the total haze and internal haze were measured in accordance with JIS K 7136. The total haze was measured in air, and the internal haze was measured in cyclohexanol solvent. This measurement was performed at five arbitrary points on the test piece, and the average value of the data at these five points was taken as the measured value. The results are shown in Table 2.
[0106] <Heat resistance: Heat seal resistance (shrinkage resistance after heat sealing)> Two test pieces, each 150 mm long and 30 mm wide, were cut from the multilayer biaxially stretched film. The length direction of the film was set to correspond to the machine direction (MD) in the original film production process. Two of the obtained test pieces were overlapped with the B2 layers (the B layer not in contact with the A layer) facing each other, and heat sealed for 1 second using a heat sealer at a temperature of 180°C and a gauge pressure of 0.2 MPa. The length and width of the test piece before and after heat sealing were measured using a caliper, and the TD shrinkage rate (%) was calculated using the following formula. The results are shown in Table 2. Shrinkage rate in TD direction = (LT0-LT1) / LT0 x 100 (%) [LT0: width of test piece before heat sealing, LT1: width of test piece after heat sealing]
[0107] <Sealability: Heat seal strength (HS strength) measurement method> The heat seal strength was measured by the following method. Two sheets of the multilayer biaxially stretched film thus produced were stacked so that the B2 layer (the B layer not in contact with the A layer) was on the inside, the lower seal bar was set to 70°C, the upper seal bar was set to 160°C, and the seal bar was heat sealed at a width of 5 mm for 0.2 seconds at a pressure of 0.2 MPa, and then allowed to cool to obtain a sealant film. Next, the sealant film was cut out to a width of 15 mm so as to include the heat-sealed portion from the obtained sealant film to obtain a test piece. The peel strength (N / 15 mm) of the obtained test piece was measured when the heat-sealed portion was peeled off in the 180° direction at a crosshead speed of 300 mm / min. The results are shown in Table 2.
[0108] [Table 2]
[0109] The stretched films of Comparative Examples 1, 3 and 4 had good stretchability, but did not have the heat resistance expected in the present invention, as the films shrunk significantly after heat sealing. On the other hand, it is seen that the present invention has good stretchability and is excellent in heat resistance, particularly heat seal resistance (low shrinkage during heat sealing).
Claims
1. It includes layer A and layer B, The A layer is 75 to 99% by mass of a 4-methyl-1-pentene polymer (A1) satisfying the following requirements (A1-I) and (A1-II); 1 to 25% by mass of a 4-methyl-1-pentene copolymer (A2) satisfying the following requirements (A2-I) and (A2-II) (where the total of the polymer (A1) and the copolymer (A2) is taken as 100% by mass), A multilayer biaxially stretched film comprising a resin composition comprising: Requirement (A1-I): The content of the structural unit (U1) derived from 4-methyl-1-pentene is 90.0 to 100 mol %, and the content of the structural unit (U2) derived from an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0.0 to 10.0 mol % (the sum of the structural units (U1) and (U2) is 100 mol %). Requirement (A1-II): Melting point (Tm A1 ) is 200 to 250°C. Requirement (A2-I): The content of the structural unit (U3) derived from 4-methyl-1-pentene is 65.0 to 96.0 mol %, and the content of the structural unit (U4) derived from an α-olefin having 8 to 20 carbon atoms is 4.0 to 35.0 mol % (provided that the total of the structural units (U3) and (U4) is 100 mol %). Requirement (A2-II): Melting point (Tm A2 ) is not observed or is 100 to 199°C.
2. The multilayer biaxially stretched film according to claim 1, wherein the structural unit (U2) is a structural unit derived from an α-olefin having 8 to 20 carbon atoms.
3. 3. The multilayer biaxially oriented film of claim 1 or 2, wherein the B layer comprises two or more layers.
4. 3. The multilayer biaxially oriented film of claim 1 or 2, wherein the B layer comprises a polypropylene layer.
5. The multilayer biaxially stretched film according to claim 1 or 2, wherein the 4-methyl-1-pentene polymer (A1) further satisfies the following requirement (A1-III): Requirement (A1-III): Intrinsic viscosity [η] measured in decalin at 135 ° C. A1 is 0.5 to 5.0 dl / g
6. The multilayer biaxially stretched film according to claim 1 or 2, wherein the 4-methyl-1-pentene copolymer (A2) further satisfies the following requirement (A2-III): Requirement (A2-III): Intrinsic viscosity [η] measured in decalin at 135 ° C. A2 is 2.0 to 6.0 dl / g
7. The multilayer biaxially stretched film according to claim 1 or 2, wherein the areal stretching ratio is 30 to 60 times.
8. 3. The multilayer biaxially oriented film according to claim 1, which is a packaging film.
9. A step (1) of obtaining a raw film including layers that will become the A layer and the B layer; and (2) stretching the raw film at an areal magnification of 30 to 100 times; The step (2) includes a step of stretching in the MD direction at 3 to 10 times and a step of stretching in the TD direction at 3 to 10 times. A method for producing the multilayer biaxially stretched film according to claim 1 or 2.
Citation Information
Patent Citations
Surface protecting film
JP2006116769A
Surface protective film
JP2010275340A
Multilayer biaxially oriented film
JP2018144351A
Multilayer biaxially oriented film and transfer film
JP2019001139A
Cited By
JPWO2025205289A1
Biaxially-oriented polyolefin film
WO2025205289A1